Effects of mixed-cooling strategies on executive functions in simulated tennis in hot and humid conditions - Wen, Minglang; Liu, Guozheng; Li, Wencan; Xie, Tao; Zhang, Yukun; Qin, Fei; Zhao, Jiexiu (Frontiers in Physiology, 2022)
This study aimed to investigate the effects of mixed-cooling strategies, which combines external (cooling vest + neck cooled collar) and internal cooling (cold sports drink ingestion) on measures of executive function during simulated tennis in hot/humid conditions. In a counterbalanced design (randomised order), eight males undertook two trials (one with the mixed-cooling strategy, [MCOOL condition] and another without [CON condition]) in a climate chamber (36.5 °C, 50% relative humidity). All subjects completed an intermittent treadmill protocol simulating a three-set tennis match with a 90-second break during odd-numbered games and 120-second breaks between sets, in accordance with the activity profile and International Tennis Federation rules. The mixed-cooling strategies were adopted before test and break time during the simulated tennis match. Stroop task, 2-back task, More-odd shifting task, gastrointestinal temperature (Tgi), skin temperature, blood lactic acid (BLA), heart rate, urine specific gravity (USG), sweat rate (SR), thermal sensation (TS) and perceived exertion (RPE) were measured. Results showed that the mean exercise time was longer in the MCOOL condition than in the CON condition. The SR was greater in CON trial compared with that in MCOOL trial. Results of two-way analysis of variance with repeated measures revealed that time×condition interactions were significant in BLA, Stroop response time, and switch cost of the more-odd shifting task. There were main effects of condition for Tgi, HR, TS, RPE, BLA, Stroop response time, and switch cost of the more-odd shifting task. In a hot/wet environment, pre- and intermittent mixed-cooling strategies can significantly improve exercise time and measures of executive function of tennis players in a simulated tennis match.